Optimizing Online Transportation Efficiency with a Value Chain Taguchi Method Approach - Rini Mulyani Sari; Evan Nugraha (Jurnal Manajemen Industri dan Logistik, 2025)
This study explores how applying the Taguchi method as a robust design tool can strengthen value chain integration in Indonesia’s ride-hailing services. A survey of 162 users was conducted, with responses examined through factor allocation, variance analysis, and a structured quality control cycle covering verification, validation, implementation, feedback, documentation, and reporting. The findings highlight several service quality drivers: timely response during peak demand, transparent pricing, convenient digital payments, and dependable customer support. The results reveal gaps between actual operations and customer expectations, underscoring the need for tighter alignment. By positioning the Taguchi method within a service-based value chain, this research introduces a novel contribution, demonstrating how quality design principles traditionally applied in manufacturing can enhance efficiency, resilience, and customer satisfaction in the competitive ride-hailing sector.